A numerical and experimental study of oblique impact of ultra-high pressure abrasive water jet. (8th March 2016) - Kang, Can; Liu, Haixia; Li, Xiuge; Zhou, Ya; Cheng, Xiaonong
An investigation of the abrasive water jet with an emphasis on the oblique impact of abrasive particles on the target plate is performed. Ultra-high jet pressure necessitates a close examination of the phenomena featured by small spatial and temporal scales. The effect of oblique impact is assessed from both numerical and practical aspects. Numerical simulation, implemented using the commercial code LS-DYNA, allows a detailed inspection of transient stress wave propagation inside the target plate. And impact experiments facilitate a qualitative description of resultant footprints of oblique water jet. Different incident angles of abrasive particles are adopted and a comparison is thereby unfolded. The results indicate that rebound, embedding, and penetration of single abrasive particle are three representative final operation states. Adjacent to the abrasive particle, the response of the target plate to oblique impact is reflected by von Mises stress distribution and plate deformation as well. Oblique impact arouses non-symmetrical stress wave distributions and distinct unbalanced node displacements at the two sides of the abrasive particle. As for the target plate, global surface morphology is in accordance with predicted effects. The most favorable surface roughness is not associated with vertical impact, and it hinges upon the selection of standoff distance. Furthermore, variation of surface roughness with incident angle is not monotonous.